2008
DOI: 10.2341/07-84
|View full text |Cite
|
Sign up to set email alerts
|

SEM Evaluation of the Hybrid Layer After Cavity Preparation with Er:YAG Laser

Abstract: SUMMARYThis study compared the thickness of the hybrid layer formed using Scotchbond Multi-Purpose Plus, Single Bond 2, Prime & Bond 2.1 and Xeno III on a dentin surface prepared with a diamond bur in a high speed handpiece or prepared with an Er:YAG laser used with two parameters of pulse energy (200 and 400 mJ) and two parameters of frequency (4 and 6 Hz). Flat dentin surfaces obtained from 20 human third molars were treated with the two methods and were then prepared with the dentin adhesive systems accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…The effects of Er:YAG laser irradiation on bond strength is controversial, reflecting the differences of experiments, adhesives used, laser settings and bond strength tests. Results from various studies have reported that the laser‐treated dentin bond strength was significantly higher than those using conventional methods (such as burs) to prepare the hard dental tissues (Aranha et al, 2007; Barceleiro et al, 2008; Comba et al, 2019; Esteves‐Oliveira et al, 2007; Ghiggi et al, 2010; Oliveira et al, 2007; Oliveira et al, 2010; Ramos et al, 2014; Ribeiro et al, 2013; Trajtenberg et al, 2004; Yazici et al, 2010; Zhang & Jiang, 2020), while other results showed no laser effect or bond strength decrease (Amaral et al, 2008; Comba et al, 2019; Esteves‐Oliveira et al, 2007; Oliveira et al, 2013; Ramos et al, 2014; Tokonabe et al, 1999; Yazici et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Er:YAG laser irradiation on bond strength is controversial, reflecting the differences of experiments, adhesives used, laser settings and bond strength tests. Results from various studies have reported that the laser‐treated dentin bond strength was significantly higher than those using conventional methods (such as burs) to prepare the hard dental tissues (Aranha et al, 2007; Barceleiro et al, 2008; Comba et al, 2019; Esteves‐Oliveira et al, 2007; Ghiggi et al, 2010; Oliveira et al, 2007; Oliveira et al, 2010; Ramos et al, 2014; Ribeiro et al, 2013; Trajtenberg et al, 2004; Yazici et al, 2010; Zhang & Jiang, 2020), while other results showed no laser effect or bond strength decrease (Amaral et al, 2008; Comba et al, 2019; Esteves‐Oliveira et al, 2007; Oliveira et al, 2013; Ramos et al, 2014; Tokonabe et al, 1999; Yazici et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…to prepare the hard dental tissues (Aranha et al, 2007;Barceleiro et al, 2008;Comba et al, 2019;Esteves-Oliveira et al, 2007;Ghiggi et al, 2010;Oliveira et al, 2007;Oliveira et al, 2010;Ramos et al, 2014;Ribeiro et al, 2013;Trajtenberg et al, 2004;Yazici et al, 2010;Zhang & Jiang, 2020), while other results showed no laser effect or bond strength decrease (Amaral et al, 2008;Comba et al, 2019;Esteves-Oliveira et al, 2007;Oliveira et al, 2013;Ramos et al, 2014;Tokonabe et al, 1999;Yazici et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion, sections were washed with distilled water and ultrasonicated for 10 min. They were then decalcified with 37% phosphoric acid for 10 s, rinsed with distilled water and deproteinized in 3% sodium hypochlorite for 60 s (Ferrari et al, 1999; De Barceleiro et al, 2008). Specimens were then rinsed with distilled water, air dried and dehydrated by immersion in ascending grades of ethanol solutions (30, 50, 70, and 90%) with a dehydration time of 5 min in each solution.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] Several applications, such as self-etching bonding agents, acid etching, primer application, and Er:YAG laser, have been introduced to control the formation and morphology of the HL. [14][15][16] Variations in protocols and conditions such as in the material composition, pH, concentration of primers, wettability, volume of water, and viscosity of the composite resin and primer might affect the thickness of the HL. 17 The thickness of the HL is reported to range from less than 1 mm for all-in-1 systems to 5 mm for conventional systems.…”
mentioning
confidence: 99%